Comprehensive Midwifery Care For Mrs “K” With A Normal Pregnancy At The Klinik Lumpangan Public Health Center - Sri Eka Juniarli; Iramaya Sari; Risnawati; Aldina Lestari; Nabila; Kurnia (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2022)
Pregnancy is a physiological condition, but in pregnancy it is important to be screened in the process of pregnancy, especially in the III trimester of pregnancy. The obstetric care provided is comprehensive care covering the processes of pregnancy, childbirth, newborns, puerperium, neonates, and birth control. Comprehensive obstetric care uses a continuous care approach by monitoring the development of the mother and fetus in monitoring the gestation period until the use of contraceptives or birth control. The methods of care in this LTA are in-person interviews, patient observations, and home visits with SOAP documentation. The subject in this upbringing was Mrs